Modelling a grid connected distributed generating photovoltaic system for the capital city of Maldives : an engineering and economic assessment - Ahmed, Mohamed Huzam (2019)
The islands of the republic of Maldives, with 80% of the land mass less than 1m above the sea level and 44% of its’ people living within 100 m of the coastline is one of the most threatened nations from sea level raise by global warming and climate change. The average sea level raise in the Maldives, recorded by the Meteorological Department of Male' International Airport is 1.7mm/year, with a maximum hourly sea level raise of approximately 7mm/year. This rate is far higher than the observed global trends in mean sea level raise. In consequence, the Maldives is well known for raising global warming and climate change to the attention of the international community, since, if the scientific warning is true, the entire country could be eradicated from the surface of earth. Considering this serious threat, the government has expressed its interest in exploring the possibility of switching from diesel to renewable sources to generate electricity. Beginning with experimental hybrid projects implemented in small islands, the government has recently started installing Photovoltaic (PV) on the rooftops of government buildings in the capital city of Male’. It has little contribution to cater the fast growing demand of electricity in Male’. Its contribution to serve the governments’ initiative to deploy Renewable Energy Technology (RETs) at large scale too, is very much limited due to the limited space available. The capital city Male’ consumes 71% of the total electricity generated by STELCO nationwide. This reflects the alarmingly high population density in the city which has a land area of just 5.8 km2; the home for ~ 42% of the population. Thus, the research, contained in this thesis, is based on modelling a gird connected Distributed Generation Photovoltaic (DGPV) system that is technically sound and financially viable, and can effectively take over partial load on the State Electric Company (STELCO)s’ national grid in Male’, which is planned to be extended to the newly build city of Hulhumale’; an island man-made to provide shelter for the homeless families in the highly populated Male’. This has not been done in any of the previous research. The hypothesis presented, justify the limitation of deploying RETs at a large scale in the Maldives from a techno-economic perspective. Despite the RET potential benefits, the study has focused on the severe constraints and challenges that would limit this change in generation technology. Based on accurate and reliable long term prediction of the future growth of electricity demand on the national grid of STELCO, the research demonstrates modelling of the proposed system using one of the most popular software, Hybrid Optimization of Multiple Energy Resources (HOMER) and the application of universally accepted design guidelines. Its economic feasibility has been done using an XL model developed by replicating the economic modeling of HOMER. The prediction of future growth on the grid for the next twenty years (2011-2030) has been made using multiple regression, one of the most widely used forecasting techniques. The predictions were validated by comparison with the results obtained from an industrial standard tool, the GMDH Shell. The modelling of the proposed supply system has been done using these predictions to identify the optimal system configuration that could meet the load requirement under the constraints specified in the simulation. HOMERs powerful sensitivity analysis feature has been used in this study to explore the energy yield that could be delivered to the grid under the constraints applied. The system being technically sound and financially viable, it represents a realistic and practical alternative solution for the energy requirement of Male’. Its implementation could be the turning point in transforming the energy sector of the country.